Urban morphology in the ipiabas district, municipality of barra do piraí - Rio De Janeiro - Júnior, Caio Flávio Martinez Fontoura [UNESP]; Pugliesi, Edmur Azevedo [UNESP]; Tachibana, Vilma Mayumi [UNESP] (My University, 2021)
The process of urban expansion has resulted in disorderly population clusters, which causes problems for the municipal administration. To mitigate this type of problem, one of the ways to reorganize the territory is in the concept of polycentrism. In this concept, there are two approaches to analyze these problems and seek solutions to them, the functional and the morphological. Concerning the morphological approach, this research work aimed the accomplishment of analyses involving income, demography, and relief, factors that may influence the structure of the urban form of Ipiabas district, a possible sub-center located in the municipality of Barra do Piraí, Rio de Janeiro. To understand the urban form, the analyzes consisted of: interpolating the location of possible residences, representing the average income per capita and the demographic density, as well as modeling a surface showing slope classes. The results show that the characteristic of the urban form of the Ipiabas district is related to topography and that there is a predominance of population settlements between the slopes.
Morfologia Urbana no Distrito De Ipiabas, Município de Barra do Piraí - Rio De Janeiro
Keywords: Kernel density estimator; Quantitative mapping; Slope; Urban centralities